DACS3: Embedding Malaysian Individual Ant Behavior in Ant Colony System - Ali Othman, Zulaiha; Md Rais, Helmi; Hamdan, Abdul Razak (World Academy of Science, Engineering and Technology (WASET.org), 2009)
Ants are fascinating creatures that demonstrate the ability to find food and bring it back to their nest. Their ability as a colony, to find paths to food sources has inspired the development of algorithms known as Ant Colony Systems (ACS). The principle of cooperation forms the backbone of such algorithms, commonly used to find solutions to problems such as the Traveling Salesman Problem (TSP). Ants communicate to each other through chemical substances called pheromones. Modeling individual ants’ ability to manipulate this substance can help an ACS find the best solution. This paper introduces a Dynamic Ant Colony System with three level updates (DACS3) that enhance an existing ACS. Experiments were conducted to observe single ant behavior in a colony of Malaysian House Red Ants. Such behavior was incorporated into the DACS3 algorithm. We benchmark the performance of DACS3 versus DACS on TSP instances ranging from 14 to 100 cities. The result shows that the DACS3 algorithm can achieve shorter distance in most cases and also performs considerably faster than DACS.